Ensuring Optimized Storage with Data Confidentiality and Privacy-Preserving for Secure Data Sharing Model Over Cloud - Rathod, Subhash; Salunke, Mangesh D.; Yashwante , Meghna; Bhende , Manisha; Rangari, Sudhir R.; Rewaskar, Vaibhav D. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper proposes privacy-preserving access control model for optimized storage over cloud. The main goal is to provide data security, privacy, integrity, and availability at a lower cost to cloud service providers while ensuring that users feel confident in trusting them. To achieve this, a secure authenticity scheme is proposed to protect data during storage and transfer over the cloud. The framework focuses on storage cost optimization while maintaining data security and authenticity. The proposed scheme compresses high-resolution images to reduce the storage size of the data by 60%. The data is then fragmented into multiple chunks, and these chunks are encrypted using the owner’s private key, providing two layers of security. Only users with authority to the data can decrypt and reconstruct it into its original format. A signature is generated to check the integrity of data. If unauthorized users attempt to update data, the auditing process can identify the compromised data. Asymmetric keys are used, and when a user uploads data to the cloud, a digital signature is created with the user’s private key. By implementing the suggested model, not only can the expenses associated with data storage be diminished through efficient data compression techniques, but it also introduces a well-defined data access protocol that prioritizes the preservation of data privacy. Experimental execution concludes that the proposed scheme has good performance over existing systems with a variety of aspects. The optimized storage and privacy-preserving access control model can be used to ensure secure data storage and sharing in collaborative cloud computing environments.